The Relationship Between Socioeconomic Status And Nutritional Status Of Toddlers In Buha Village Mapanget Sub-District Manado City (Literature Review) - Tarigan, Herdianta; Mulia Saragih, Varellisia Sandjeri; Lumbantoruan, Helmalia; Pasaribu, Riris; Sianipar, Juni; Situmeang, Exaudya (Yayasan Kita Menulis, 2023)
Nutritional status is the state of the body as a result of food consumption and nutrient use. Nutritional status is influenced by several factors, one of which is socioeconomic level. Children under five years old (toddlers) are the